2003
DOI: 10.1080/369378031000137369
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral phaeohyphomycosis in an immunodeficient child treated medically with combination antifungal therapy

Abstract: Cerebral phaeohyphomycosis is a rare fungal infection with a poor prognosis when using conventional antifungal therapy in the absence of neurosurgical intervention. We present a case of a pediatric patient with inoperable Cladophialophora bantiana cerebral abscesses. To our knowledge, this child's case is the first reported to be treated with the combination of the newer triazole voriconazole and the new echinocandin caspofungin. Although our patient subsequently died, the natural rapid progression of the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…modesta (n ϭ 1) scribed. Patients with bone marrow and solid organ transplantation and patients who are on steroid therapy are particularly affected (2,13,15,24,31,35,36,51,54,57). Cladophialophora bantiana, a neurotropic fungus, has rarely been isolated from sources other than clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…modesta (n ϭ 1) scribed. Patients with bone marrow and solid organ transplantation and patients who are on steroid therapy are particularly affected (2,13,15,24,31,35,36,51,54,57). Cladophialophora bantiana, a neurotropic fungus, has rarely been isolated from sources other than clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent series of 48 patients with brain abscess due to C. bantiana showed that 35 patients (72%) had no risk factors and that only 13 patients (28%) survived the infection, despite combined surgical and antifungal treatment (48). The minority of immunocompromised patients are transplant recipients, intravenous drug abusers, or individuals on steroids (2,13,15,24,31,35,36,51,54,57,59).…”
mentioning
confidence: 99%
“…Mortality was Ͼ70%. Since that review in 2004, over 50 cases have been reported, with C. bantiana remaining the most frequently seen isolate (131,4,17,16,22,31,40,70,78,93,121,139,170,189,243,244,268,272,276,328,332,341,363,380,399,420,433,448,450,467,476,545,575,636,657,696,700,721,731,733,754,759). A new species, Fonsecaea monophora, has been reported since that time and appears to have a predilection for causing CNS disease, in contrast to its related species, F. pedrosoi (420,721,733).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…Amphotericin B (AmB) alone or in combination with flucytosine (5FC), VRC, or ITC was not completely satisfactory (14,149). However, the triple combination of AmB, 5FC, and ITC was associated with improved survival in a few cases of systemic phaeohyphomycosis (90 (162)(163)(164). Notably, combination antifungal therapy is recommended for cerebral abscesses when surgery is not possible and for disseminated infections in immunocompromised patients (149).…”
Section: Recommended Diagnostics and Treatment Approachesmentioning
confidence: 99%